PENGARUH SIMPEG, KEPEMIMPINAN DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM KALIMANTAN SELATAN - Mazidah - (KINDAI, 2023)
ABSTRACTThe purpose of this study was to prove and analyze the significant influence simultaneously, partially and dominantly between personnel management information systems, leadership and supervision on employee performance at the Regional Office of the Ministry of Law and Human Rights in South Kalimantan. The research design includes quantitative research using survey methods. This research was designed as a correlational study or to find out whether there is an influence on each independent variable on the dependent variable both together and separately. The population in this study were all civil servant employees at the Regional Office of the Ministry of Law and Human Rights in the Province of South Kalimantan, totaling 137 people, then the sample was determined with a leeway level of 5% using the Slovin formula so that there were 103 employees as respondents. Data collection techniques using a questionnaire that has met the requirements of the validity and reliability tests, using regression analysis. The results of the study show that: 1). There is a simultaneous influence of the personnel management information system (simpeg), leadership, and supervision of employee performance at the Regional Office of the Ministry of Law and Human Rights in South Kalimantan. 2). Personnel management information systems have a partial effect on employee performance, supervision also has a significant partial effect on performance, while leadership has no effect on performance, this shows that good or bad leadership does not always cause changes in employee performance 3). The monitoring variable has the most dominant influence significantly on employee performance at the Regional Office of the Ministry of Law and Human Rights in South Kalimantan.Keywords: Personnel Management Information System, Leadership,and Supervision on Employee Performance